Editorial: Beyond Terrorism and Sexual Slavery: Dynamics of armed conflicts, trafficking, and forced migration - Hurtado, Mónica (Anti-Trafficking Review, 2024)
This Editorial introduces a Special Issue of Anti-Trafficking Review on the theme of armed conflicts and their relationships with and impact on human trafficking, forced migration, and exploitation. It provides an overview of the literature on this theme, which has primarily focused on terrorism and sexual slavery. It then outlines the articles in the Special Issue, which expand our understanding of the topic by adding nuances to the experiences of people who flee, or choose to remain in, conflict-affected areas.